2022
DOI: 10.1101/2022.11.10.515365
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A tracheal aspirate-derived airway basal cell model reveals a proinflammatory epithelial defect in congenital diaphragmatic hernia

Abstract: Rationale: Congenital diaphragmatic hernia (CDH) is characterized by incomplete closure of the diaphragm and lung hypoplasia. The pathophysiology of lung defects in CDH is poorly understood. Objectives: To establish a translational model of human airway epithelium in CDH for pathogenic investigation and therapeutic testing. Methods: We developed a robust methodology of epithelial progenitor derivation from tracheal aspirates of newborns. Basal stem cells (BSCs) from CDH patients and preterm and term, non-CDH c… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 65 publications
1
1
0
Order By: Relevance
“…Using immunofluorescence on autopsy samples, we confirmed that human fetuses with CDH also have an inflammatory status with macrophage enrichment and increased TNFα and pNF-κB expression. A similar observation was made in neonates with CDH postnatally, who were found to have upregulation of pNF-κB in the proximal lung (basal cells) and TNFα in the distal lung ( 57, 58 ). Other studies reported that neonates with CDH had high levels of proinflammatory cytokines in the blood postnatally ( 5964 ).…”
Section: Discussionsupporting
confidence: 74%
“…Using immunofluorescence on autopsy samples, we confirmed that human fetuses with CDH also have an inflammatory status with macrophage enrichment and increased TNFα and pNF-κB expression. A similar observation was made in neonates with CDH postnatally, who were found to have upregulation of pNF-κB in the proximal lung (basal cells) and TNFα in the distal lung ( 57, 58 ). Other studies reported that neonates with CDH had high levels of proinflammatory cytokines in the blood postnatally ( 5964 ).…”
Section: Discussionsupporting
confidence: 74%
“…With these techniques, we validated the presence of amniotic fluid epithelial cells (AFEC), highlighting that these shed from a multiplicity of developing tissues, and demonstrating that this population contains progenitors capable of forming tissue-specific primary fetal organoids. Finally, with the adoption of fetal surgery procedures such as Fetal Endoluminal Tracheal Occlusion (FETO) to treat CDH, we can now sample and expand viable epithelial cells from tracheal fluid (TF) at various stages in the therapy [39][40][41] .…”
Section: Introductionmentioning
confidence: 99%